A modification of intraluminal middle cerebral artery occlusion/reperfusion model for ischemic stroke with laser Doppler flowmetry guidance in mice - Cai Q; Xu G; Liu J; Wang L; Deng G; Liu J; Chen Z (Neuropsychiatric Disease and Treatment)
Qiang Cai,1,* Gang Xu,2,* Junhui Liu,1 Long Wang,1 Gang Deng,1 Jun Liu,3 Zhibiao Chen1 1Department of Neurosurgery, Renmin Hospital of Wuhan University, Wuhan, 2Department of Neurosurgery, Xiantao First People’s Hospital, Xiantao, 3Department of Emergency, The Central Hospital of Wuhan, Wuhan, Hubei, People’s Republic of China *These authors contributed equally to this work Abstract: Stroke is one of the common causes of death and disability in the world. The intraluminal middle cerebral artery occlusion/reperfusion (MCAO/R) model is a “gold standard” in surgical ischemic stroke models. Here, we optimized the procedure of this model by ligating on external carotid artery (ECA) stump and two ligatures prepared on internal carotid artery, which could improve the success and survival rate in mice. The results show that ECA approach was superior to common carotid artery approach. Meanwhile, we found that the exposure of pterygopalatine artery was not an essential step for MCAO/R model in mice. Keywords: middle cerebral artery occlusion, ischemia stroke, animal model, mice